STUDY OF SOLUTIONS PROPERTIES OF RECONSTRUCTION VEHICLES PROBLEMS BY THE OPTIMIZATION METHOD LAGRANGE - Bosov, A. A.; Pikh, B. P. (Science and Transport Progress, 2005)
The tasks of reconstruction of vehicles are formulated as the problems of vector optimization. The authors have proposed a method of constructing the three solution of conventional extremum tasks with the use of technological & economic card. The solution, obtained with the use of Lagrange function, is a prominent combination for the points of precise solution.